How AI Navigates the Ethical Minefield of Medical Conflicts of Interest - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
The rapid integration of Artificial Intelligence AI into healthcare promises immense benefits but introduces complex ethical challenges, particularly concern...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Clinical Decision Support